Time of Day-Dependent Alteration of Hippocampal Rac1 Activation Regulates Contextual Fear Memory in Rats - Jiang, Lizhu; Liu, Chao; Zhao, Baizhen; Ma, Chen; Yin, Yan; Zhou, Qixin; Xu, Lin; Mao, RongRong (Frontiers in Molecular Neuroscience, 2022)
Fear memory in species varies according to the time of the day. Although the underlying molecular mechanisms have been extensively explored, they remain largely unknown. Here, we report that hippocampal Rac1 activity undergoes a time of day-dependent alteration both in nocturnal rats and diurnal tree shrews and that training at the lower hippocampal Rac1 activation period during the night leads to better contextual fear memory in rats. Furthermore, day and night reversion by 24 h darkness/24 h light housing inverses the external clock time of hippocampal Rac1 activation, but the better contextual fear memory still coincides with the lower Rac1 activation in rats during the night. Interestingly, exogenous melatonin treatment promotes hippocampal Rac1 activity and impairs better contextual fear memory acquired at the lower Rac1 activation period during the night, and Rac1-specific inhibitor NSC23766 compromises the effect of melatonin. These results suggest that the time of day-dependent alteration of hippocampal Rac1 activation regulates contextual fear memory in rats by forgetting.